(3GdhGaj HGdhajGJs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3bS Hf SGYOI GdCjGOi s
(3BNQgG (B:s
(3bHGH Hf CKje GddjKi , Ke LRA ef MQa GddGe hajg GdCSeGA Ke LRA ef MQa Gdeje Chdg (B: (3GHf efGPQ Ke LRA ef MQa GdgGA Chdg (B: (3gRGQ Ke LRA ef MQa GdjGA hChdg jYbhH hjfJgi HfgGjI GdLRA s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B32 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B174 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI eUhQI Yf fSNI ecJHI fhQ YKeGfjI HESJGfHhd (B1391) ((3JGQjN (B1219) s
Keywords: (3GdJGQjNs